Sharp Profile for Icebreaking Propellers to Improve Their Ice and Hydrodynamic Characteristics - Alexander Vladislavovich Andryushin; Sergey Vladimirovich Ryabushkin; Alexander Yurievich Voronin; Egor Vladimirovich Shapkov (Journal of Marine Science and Engineering, 2022)
Stern-first operation under severe ice conditions (ridges) is one of the most effective modes to increase the operating efficiency of icebreakers and ice ships. However, when a ship overcomes the ridge astern, the propellers continuously interact with ice blocks, and ice moment affects the propeller and the main engine. This leads to propeller speed drop and propeller thrust reduction. Propeller stop is also possible. This is the reason why the propeller ice moment needs to be decreased. Blade profiles with a sharp leading edge are used for this purpose because their thickness is significantly less than that of a traditional icebreaking profile. The application of sharp profiling makes it possible to significantly reduce the ice moment (ice loads) on the propeller, reduce the drop in its speed, and increase the hydrodynamic thrust. The main task when installing blades with sharp profiles is to ensure the strength of their leading edges exposed to ice pressure. In this article, the authors tackle upon some methods of assigning integral and local ice loads on propellers. Solutions for ensuring the local strength of the blade edges were developed and presented. The influence of sharp profiling on the hydrodynamic and cavitation characteristics of ice propellers was considered. The article presents examples of calculating the hydrodynamic propeller thrust and moment, as well as ice loads on a propeller with a sharp and traditional profile, when an ice ship moves through a ridged ice isthmus with its stern first.